Photoelectroreduction of Building‐Block Chemicals. (21st April 2017) - Chen, Fengjiao; Cui, Wei; Zhang, Jie; Wang, Yeyun; Zhou, Junhua; Hu, Yongpan; Li, Yanguang; Lee, Shuit‐Tong
Abstract: Conventional photoelectrochemical cells utilize solar energy to drive the chemical conversion of water or CO2 into useful chemical fuels. Such processes are confronted with general challenges, including the low intrinsic activities and inconvenient storage and transportation of their gaseous products. A photoelectrochemical approach is proposed to drive the reductive production of industrial building‐block chemicals and demonstrate that succinic acid and glyoxylic acid can be readily synthesized on Si nanowire array photocathodes free of any cocatalyst and at room temperature. These photocathodes exhibit a positive onset potential, large saturation photocurrent density, high reaction selectivity, and excellent operation durability. They capitalize on the large photovoltage generated from the semiconductor/electrolyte junction to partially offset the required external bias, and thereby make this photoelectrosynthetic approach significantly more sustainable compared to traditional electrosynthesis.